Analisis Komparatif: Pengaruh Makroekonomi pada Kinerja Reksa Dana Saham Syariah dan Konvensional - Ridwan, Muhamad Faisal Pasha; Mai, Muhamad Umar (Journal of Islamic Economics and Business, 2022)
This study aims to compare the performance of Islamic stockÂ mutual funds and conventional stock mutual funds withÂ different operating systems so that can be recommended forÂ investors in choosing the type of mutual fund. This study alsoÂ aims to determine the effect of macroeconomic factors onÂ the performance of these equity funds. The sample used inÂ this study were 5 investment manager companies that issuedÂ Islamic stock mutual fund products and conventional stockÂ mutual funds in the 2010-2019 period and were selectedÂ through purposive sampling technique. This type of researchÂ is quantitative research. The data used is secondary dataÂ obtained from OJK published reports. The results of thisÂ study indicate that there is no significant difference betweenÂ the performance of conventional equity mutual funds andÂ Islamic stock mutual funds. In addition, three independentÂ variables in the study, namely inflation rate, exchange rate,Â and interest rate have a significant effect on the performanceÂ of Islamic equity mutual funds. For conventional equityÂ mutual funds, the results show that the inflation rate andÂ interest rate variables have a significant effect, while theÂ exchange rate variable has a negative but not statisticallyÂ significant effect on the performance of conventional equityÂ mutual funds.